Effect of Npk Dosage and Type of Ameliorant on Growth and Yield of Large Red Chili Plants (Capsicum annum L) - Muhidin, Rahmat; Ria, Elly Roosma; Amalia, Lia (Institute of Computer Science (IOCS), 2023)
This study aims to study the interaction between NPK doses and types of ameliorant on the growth and yield of red chili plants and to obtain the optimum dose of NPK for each type of ameliorant that gives maximum yield of red chili. The experiment was conducted in the experimental garden of Padjadjaran University, Jatinangor District, Sumedang Regency from September to December 2021. The method used in this study was verification with an experimental approach using the Split Plot Design (SPD) consisting of two treatment factors. The first factor as the main plot was pearl NPK Fertilizer (N) which consisted of 3 treatment levels namely n1 (5 g L-1), n2 (7.5 g L-1), and n3 (10 g L-1). The second factor was the type of ameliorant (P) as a subplot consisting of 3 treatment levels, namely p0 (without ameliorant), p1 (amelioran 4 tons Ha-1), p2 (bioamelioran 4 tons Ha-1) so that there were 9 combinations of treatments each in repeat 3 times. There was an interaction between NPK dose and type of ameliorant on growth (plant height, number of leaves, stem diameter 3 and 4 WAP, root length 5 WAP and root decay ratio) and yield of chili plants (fruit weight per plant).